Causal factors affecting the smartphone addiction of generation Z in Bangkok during the COVID-19 pandemic - Prasittichok, Pitchada; Sripairote, Thanawat; Trisri, Sarawut (Humanities, Arts and Social Sciences Studies, 2023)
The objectives of this research were to understand the smartphone addiction of Generation Z (Gen Z) in Bangkok, Thailand and investigate the causal factors in smartphone addiction among this sample group during the 2019 Coronavirus (COVID-19) pandemic. A sequential exploratory design was adopted in this study. In the qualitative phase, five Gen Z informants living in Bangkok and addicted to smartphones participated in interviews. In the quantitative phase, multistage sampling was employed for the sample selection, which consisted of 400 respondents who exhibited smartphone addiction and lived in Bangkok. The following instruments were used: 1) smartphone addiction scale: Thai short version, 2) the Thai version of the self-regulation scale, 3) the Thai multi-dimensional scale of perceived social support, 4) the new media literacy scale: Thai version, and 5) the Thai version of the Alabama parenting questionnaire short form. The Cronbach’s alpha coefficients equaled 0.87, 0.84, 0.89, 0.75, and 0.79, respectively. Structural equation modeling was used to analyze the data. The results revealed that the factors associated with smartphone addiction were personal factors, such as new media literacy and self-regulation, and environmental factors, such as social support and parenting style. Moreover, the hypothesized model was considered to be suitable for predicting smartphone addiction among Gen Z respondents based on the following statistics: Chi-square = 36.31, p = 0.07, df = 25, Chi-square/df = 1.45, SRMR = 0.03, RMSEA = 0.03, CFI = 1.00, and GFI = 1.00. New media literacy, perceived social support, and parenting significantly influenced self-regulation, which in turn influenced smartphone addiction. After considering R2, the prediction of smartphone addiction by causal factors and self-regulation were 94% and 46%, respectively. This study proposes the implementation of additional educational programs that focus on enhancing media literacy, fostering self-regulation, and encouraging social support. Moreover, these results may provide valuable information to support the creation of effective intervention approaches to facilitate clinical programs for addiction rehabilitation which promote healthier lifestyles as a means of regulating smartphone usage.